Scaling effects on the dynamic characteristics of long-wavelength vertical-cavity surface-emitting lasers (VCSELs) - YAP, D; KOH, S; TIONG, S (ELSEVIER SCI LTD, 2008)
The influence of the oxide aperture radius oil the characteristics of a long-wavelength vertical-cavity surface-emitting laser (VCSEL) lasing at 1550nm is presented in this paper. While previous works in the literature mostly investigate the scaling effects of short-wavelength VCSELs. The importance of studying the effects of long-wavelength operation should not be underestimated, as it could be used in fiber optics communication to mitigate dispersion and attenuation of the channel. Using the oxide-confined VCSEL model, the dynamic operations were examined taking into account the carrier-noise, photon-noise and phase-noise, including feedback of the external cavity. Our simulations show that by reducing the oxide aperture up to a given optimal radius, an improvement in the device's characteristics can be demonstrated. Below this value, performance degradation is expected due to increased diffraction losses, reduced confinement factor and enhanced spontaneous emission. (c) 2007 Elsevier Ltd. All rights reserved.